Gravitational effects of Nix and Hydra in the external region of the Pluto-Charon system - Pires dos Santos, P. M. [UNESP]; Giuliatti Winter, S. M. [UNESP]; Sfair, R. [UNESP] (Wiley-Blackwell, 2011)
Two new companions to the Pluto-Charon binary system have been detected in 2005 by Weaver et al. These small satellites, named Nix and Hydra, are located beyond Charon's orbit. Although they are small when compared to Charon, their gravitational perturbations can decrease the stability of the external region (beyond Charon's orbit). The dynamical structure of this external region is analysed by numerically simulating a sample of particles under the gravitational effects of Pluto, Charon, Nix and Hydra. As expected the effects of Nix and Hydra decrease the external stable region. Agglomerates of particles can survive even after 105 orbital periods of the binary in some regions, such as coorbital to Nix and Hydra and between their orbits. We also analysed the effects of hypothetical satellites on the orbital evolution of Nix and Hydra in order to constrain an upper limit size. Some hypothetical satellites can be coorbital to Nix or Hydra without provoking any significant gravitational effects on them.
Keywords: Kuiper belt: general; planetary systems